Increasing the wear resistance of a radial bearing with a non-standard support profile and polymer coating on the shaft surface taking into account the pressure-viscosity ratio - Khaidar N. Abdulrakhman; Viktoria I. Kirishchieva; Murman A. Mukutadze; Valentina E. Shvedova (Frontier Materials & Technologies, 2022)
The paper covers the development and analysis of a model of the true viscous lubricant movement in the working gap of a radial sliding bearing with a non-standard support profile having a fluoroplastic composite polymer coating with a groove on the shaft surface. The authors obtained new models based on the classical equation in the approximation for the “thin layer” and the continuity equation describing the laminar pattern of movement of a lubricant with the viscous rheological properties. The results of the numerical analysis of the developed models allowed obtaining a quantitative assessment of the efficiency of the bearing bush support profile and the polymer-coated shaft with an axial groove. To complete the set of studies and verify theoretical insights, the authors carried out the experimental research. The novelty of the work lies in the development of an engineering calculation technique that allows determining the magnitude of the main tribotechnical parameters of a radial sliding bearing (hydrodynamic pressure, load capacity, and friction ratio) and expanding the area of practical application of the developed engineering calculations. The design of the radial bearing with a fluoroplastic antifriction composite polymer coating, a 3 mm wide groove, and a special support profile ensured the stable shaft ascent on the hydrodynamic wedge, which experimentally confirmed the correctness of the results of theoretical studies of sliding bearings with a diameter of 40 mm at a sliding speed of 0.3–3 m/s and a load of 13–65 MPa.